2021
DOI: 10.1029/2020jb021624
|View full text |Cite
|
Sign up to set email alerts
|

Complicated Lithospheric Structure Beneath the Contiguous US Revealed by Teleseismic S‐Reflections

Abstract: The structure of the lithosphere-asthenosphere system is fundamental to understanding plate tectonics and Earth's evolution. Continental lithosphere, which is far more complicated than its oceanic counterpart due to the imprints left by numerous geologic processes during its long life, has drawn great attention from the seismological community (e.g.,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
69
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(79 citation statements)
references
References 39 publications
10
69
0
Order By: Relevance
“…Wang et al, 2022). (c) Receiver function studies revealed a relatively shallow Moho and shallow lithosphere-asthenosphere boundary beneath the NMSZ (T. Liu & Shearer, 2021;Ma & Lowry, 2017;McGlannan & Gilbert, 2016), which reflects a weak and thinned lithosphere. Moreover, Thomas and Powell (2017) proposed that most intraplate seismic zones are developed from ancient rifts or tectonic sutures, which happened for all the three seismic zones (i.e., NMSZ, ETSZ, and SCSZ) in the CEUS.…”
Section: Formation Of the Intraplate Seismic Zonesmentioning
confidence: 99%
“…Wang et al, 2022). (c) Receiver function studies revealed a relatively shallow Moho and shallow lithosphere-asthenosphere boundary beneath the NMSZ (T. Liu & Shearer, 2021;Ma & Lowry, 2017;McGlannan & Gilbert, 2016), which reflects a weak and thinned lithosphere. Moreover, Thomas and Powell (2017) proposed that most intraplate seismic zones are developed from ancient rifts or tectonic sutures, which happened for all the three seismic zones (i.e., NMSZ, ETSZ, and SCSZ) in the CEUS.…”
Section: Formation Of the Intraplate Seismic Zonesmentioning
confidence: 99%
“…Therefore, variations in the Ssds traveltime are primarily due to seismic structure in the upper mantle beneath the seismic stations. There is no source-side and receiver side ambiguity if the analysis is limited to earthquakes deeper than the reflecting boundaries of interest (Liu and Shearer, 2021) but the data set would be significantly smaller.…”
Section: Mapping Of the 410 And 660 By 1-d Common Reflection Point Im...mentioning
confidence: 99%
“…Due to the influence of thick sedimentary layers atop the crust in the Atlantic and Gulf coastal plains, it is difficult to reliably image crustal and upper‐mantle structure using RF analysis or surface wave tomography alone, leading to occasionally conflicting crustal thickness and lithospheric velocity measurements. Additionally, many of the recent studies on crustal and upper mantle properties either target the entire contiguous United States (e.g., Buehler & Shearer, 2017; Liu & Shearer, 2021; Ma & Lowry, 2017; Shen & Ritzwoller, 2016; Yuan et al., 2014), or along densely spaced profiles (e.g., Hopper et al., 2016; Li et al., 2020; MacDougall et al., 2015; Parker et al., 2013; Verellen et al., 2020). There are only a limited number of post‐USArray studies on crustal and mantle structure focusing on the SEUS (e.g., Biryol et al., 2016; Hopper et al., 2017; Wagner et al., 2018), among which none has used the RF and Rayleigh wave dispersion joint inversion technique that this study employs.…”
Section: Introductionmentioning
confidence: 99%
“…Surface wave tomography studies (e.g., Bensen et al., 2008; Gaite et al., 2012; Porter et al., 2016; Spica et al., 2016) image low velocity anomalies in the upper crust beneath the Gulf Coastal Plain, which are attributed to the thick sediments (up to 10 km thick, Laske & Masters, 1997). RF and seismic tomography studies indicate that compared with the SAM, the Atlantic and Gulf of Mexico coastal plains possess relatively thin crust, in the range of ∼25–35 km (Buehler & Shearer, 2017; Li et al., 2020; Liu & Shearer, 2021; Ma & Lowry, 2017; Shen & Ritzwoller, 2016). With the exception of the central Suwannee Terrane, the observed κ values in the coastal plains and most part of the Suwannee Terrane are generally greater than 1.80 (Ma & Lowry, 2017), which are higher than the global average value of 1.78 for continental crust (Christensen, 1996) and thus may indicate a mafic composition.…”
Section: Introductionmentioning
confidence: 99%